2009
DOI: 10.1016/j.neurobiolaging.2007.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Age-related accumulation of Reelin in amyloid-like deposits

Abstract: Age-related accumulation of Reelin in amyloid-like deposits Abstract Accumulating evidence suggest that alterations in Reelin-mediated signaling may contribute to neuronal dysfunction associated with Alzheimer's disease (AD), the most common form of senile dementia. However, limited information is available on the effect of age, the major risk factor of AD, on Reelin expression. Here, we report that normal aging in rodents and primates is accompanied by accumulation of Reelin-enriched proteinous aggregates in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
110
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(123 citation statements)
references
References 72 publications
13
110
0
Order By: Relevance
“…However, Nomura et al (1996) found no evidence of deposits or granular structures in SAMP8 brain although they reported an increase in APP-like immunoreactivity. From their description, the Aβ-LI and reelin deposits containing Aβ reported by Knuesel et al (2009) would appear to be the pathological granules that we have investigated further in the present study. Given that we found that they do not stain with Thioflavin S or with Hylite-AF488, and that Aβ-staining is a mistake due to the presence of the contaminant IgM, we conclude that there is no deposition of Aβ in these granular structures.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, Nomura et al (1996) found no evidence of deposits or granular structures in SAMP8 brain although they reported an increase in APP-like immunoreactivity. From their description, the Aβ-LI and reelin deposits containing Aβ reported by Knuesel et al (2009) would appear to be the pathological granules that we have investigated further in the present study. Given that we found that they do not stain with Thioflavin S or with Hylite-AF488, and that Aβ-staining is a mistake due to the presence of the contaminant IgM, we conclude that there is no deposition of Aβ in these granular structures.…”
Section: Discussionmentioning
confidence: 75%
“…The deposits described have included, among others, β/A4 protein-like immunoreactivity granular structures (β-LIGS) (Takemura et al 1993), amyloid β-peptide-like immunoreactivity deposits (Aβ-LI) (Fukunari et al 1994), reelin deposits that contained Aβ (Knuesel et al 2009) and the hippocampal granules containing Aβ(1-40) and Aβ(1-42) (Del Valle et al 2010;Currais et al 2012;Porquet et al 2013;Yamaguchi et al 2012). Morley et al (2000) found Aβ plaques that were not discernible before 16 months of age and became more prevalent at 22 months of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, an in utero immune challenge at GD17 preferentially affected the expression levels of the hippocampal NR1 subunit of the NMDA receptor as compared to GD9 and control treatments, which were paralleled by impairments in working memory performance. These studies revealed also that a prenatal immune challenge during late gestation resulted in acceleration of aging, as indicated by the earlier formation of Reelin-positive extracellular amyloid-like deposits, a neuropathological feature detected in the hippocampal formation in several species that is accompanied by a reduction in Reelin-expressing neurons (Knuesel et al, 2009;Knuesel, 2010). Both neuropathological alterations significantly correlated with hippocampusdependent episodic-like memory deficits (Knuesel et al, 2009).…”
Section: Prenatal Polyi:c Model Of Accelerated Agingmentioning
confidence: 87%
“…These studies revealed also that a prenatal immune challenge during late gestation resulted in acceleration of aging, as indicated by the earlier formation of Reelin-positive extracellular amyloid-like deposits, a neuropathological feature detected in the hippocampal formation in several species that is accompanied by a reduction in Reelin-expressing neurons (Knuesel et al, 2009;Knuesel, 2010). Both neuropathological alterations significantly correlated with hippocampusdependent episodic-like memory deficits (Knuesel et al, 2009). We found that healthy and cognitively normal subjects were able to sufficiently clear and degrade these deposits, whereas cognitively impaired aged mice failed to do so.…”
Section: Prenatal Polyi:c Model Of Accelerated Agingmentioning
confidence: 92%